Alemtuzumab in refractory Sézary syndrome - Carmen María Alcántara Reifs; Rafael Salido-Vallejo; Gloria María Garnacho-Saucedo; Sofía De la Corte-Sánchez; Alberto González-Menchen; Antonio Vélez García-Nieto (Sociedade Brasileira de Dermatologia, 2016)
Abstract: Sézary syndrome is a primary cutaneous T-cell lymphoma characterized by the triad of erythroderma, lymphadenopathy and circulating atypical cells. The emergence of new molecular targets has enabled the development of drugs such as alemtuzumab, an anti-CD52 monoclonal antibody, which has shown promising results in the treatment of this entity. We report the case of a 70-year-old male with refractory Sézary syndrome in whom treatment with alemtuzumab achieved an 80% skin lesion clearance with complete haematologic and radiologic response. The treatment was discontinued after 4 months due to adverse effects, with the patient showing a sustained response without disease progression after 13 months of follow-up.